Effect of magnetic field and arbuscular mycorrhizal fungi on germination and growth of tomato (Lycopersicon esculentum Mill.) - Anne Nurbaity; Anne Nuraini; Eleonora Agustine (Asosiasi Mikoriza Indonesia, 2022)
Agricultural technology innovation such as application of low magnetic field and arbuscular mycorrhizal fungi (AMF) could improve growth of some vegetable plants, such as tomatoes.The objectives of the research were to determine: (1) the effect of low magnetic field treatment on germination of tomato seeds, and (2) the combined effect of mycorrhiza and magnetic field treatments on growth of tomato plants. The first experiment was conducted in the laboratory to test the germination of magnetized and non-magnetized seeds on different growing mediums. The second experiment was conducted in a screenhouse using Randomised Blocked Design with the treatments of exposure of magnetic field (0 and 0.2 mT) and AMF (Glomus sp., Gigaspora sp. and Combination of Glomus sp. and Gigaspora sp.). Both treatments were applied as pre-sowing seed treatments. Results revealed the exposure of seeds to magnetic fields increased the seedling germination percentage, especially in the treatments combined with Gigaspora sp. (90%). Further measurement of plant heights showed that magnetized seeds consistently showed a higher plant height compared to non-magnet treatments. Gigaspora sp. which applied either as single or in mixture with Glomus spp. have shown better effect than Gigaspora sp. alone on the growth of tomatoes